A phenomenological study of nightclub visitor lifestyles and their role in shaping urban night tourism in yogyakarta - Fera Dhian Anggraini; Azis Fitri Profita Aznam; Winda Rosita Dewi (Surya Hijau Manfaat, 2026)
This study aims to identify the lifestyle patterns of nightclub visitors based on observational data and in-depth interviews with 25 participants at prominent nightclubs in Yogyakarta. The research employed a qualitative approach with a phenomenological design and was analyzed using NVivo software. The findings reveal three dominant themes in the lifestyle of nightclub visitors in Yogyakarta: culture and norms, hedonism, and representation and self-validation. A distinctive finding shows that visitors actively negotiate between pleasure-seeking behavior and strong local socio-cultural expectations. As a city widely recognized as a student and cultural center, Yogyakarta’s nightlife reflects a pattern of self regulation in which visitors seek enjoyment while maintaining social respectability. These findings provide empirically grounded insights into the unique characteristics of Yogyakarta’s urban night tourism and offer references for developing more adaptive, culturally sensitive, and safe nightlife management strategies.